Day and Night Thermal Mass Performance Studies on Wetland Settlement in Palembang. Issue 1 (February 2021) - Triyuly, Wienty; Triyadi, Sugeng; Wonorahardjo, Surjamanto
Abstract: The phenomenon of urban heat island was affected by the thermal mass of the area. The massive development of settlement in the wetland of Palembang had changed the natural thermal mass composition. This paper discussed the effect of the settlement development in the urban thermal environment of the wetland of Palembang. We measured the effect of building, pavement, water body and vegetation factors in the day and night air temperature of the settlement area. Direct field measurement was done using the wet and dry thermometer, anemometer and globe thermometer for 3x24 hours. The result showed that there were differences in day and night air temperature in the area with different thermal mass composition. It was also affected by wind direction and weather conditions. We concluded that the day and night temperature balance of the area could be control by the composition of thermal mass in the settlement area.